KONFLIK BATIN TOKOH-TOKOH UTAMA ANTOLOGI CERPEN PENGANTIN LUKA KARYA K.USMAN - Putri Kartika Sari, Putu Diah (Humanis; Volume 4. No. 3. September 2013, 2013)
This article analyzes the psychological aspect of the main characters in six short stories from the book Pengantin Luka written by K.Usman. From the fifteen short stories from the book, six are chosen because they have a same theme that is marriage. Theory of psychology of literature is used to analyze those short stories as the main characters involve in the internal conflict within themselves which rose because of id, ego and superego. The characters are Tantini, Sarinah, Karel, Gadis, Nabila, and Maligum posses the giving way and sincere feeling, sadness and longing, faith and wait, selecting a partner, honesty and lies, even a real and fake happiness. Human beings always catches for happiness and ignores the tension so that they can’t make the differentiation between fantasy and reality. Marriage for some people is the most wanted and the happiest thing but this short story revealed another side of marriage. A bride is couples of human that have been committed to the marriage. Wound is a painful feeling because of the pain.
Keywords: short story, psychological literature, internal conflict